Prevalence of chronic myocarditis in patients with atrial fibrillation according to the results of a single-center study - E. A. Archakov; R. E. Batalov; M. S. Khlynin; M. A. Dragunova; E. S. Sitkova; O. R. Eshmatov; T. V. Moskovskikh; S. Yu. Usenkov; I. V. Stepanov; S. A. Afanasyev; S. V. Popov (Рациональная фармакотерапия в кардиологии)
Aim. To assess the incidence of chronic myocarditis in patients with atrial fibrillation.Material and methods. The study included 145 patients. The majority of patients were male — 118 (81.4%). The median age was 45 (38; 50) years. Most had paroxysmal AF — 60 (41.4%), slightly fewer had persistent AF — 55 (37.9%), 30 (20.7%) patients had long-term persistent AF. All patients underwent radiofrequency ablation of AF and endomyocardial biopsy (EMB) with subsequent histological and immunohistochemical studies (IHC). Morphological verification of myocarditis was performed in accordance with the Dallas criteria modified by the World Heart Federation.Results. Signs of chronic myocarditis were identified in 64 patients (44.1%). The median age of patients with myocarditis was 44 (36.5;49) years, without myocarditis — 46 (38;51) years. In men, myocarditis was detected in 50 cases (42%), in women — in 14 (51.9%). In paroxysmal AF, myocarditis was detected in 25 patients (41.7%), in persistent AF — in 23 (41.8%), and in long-term persistent AF — in 16 (53.3%). The groups with and without chronic myocarditis were comparable when compared based on the main echocardiographic parameters. Regression analysis did not show a significant influence of these factors on the probability of detecting chronic myocarditis in patients with AF. In patients under 30 years of age, there were no signs of inflammation without the presence of myocardial fibrosis, while the maximum stage of fibrosis occurred in patients from 31 to 40 years of age. The stage of fibrosis did not depend on gender. More often than others, a combination of enterovirus and herpes virus type 6 was detected in biopsy specimens. In patients over 51 years of age, biopsies generally did not express any virus on immunohistochemical studies.Conclusion. Chronic myocarditis in patients with AF was significantly more often detected in younger patients (up to 50 years inclusive), and was more common in women, as well as in the presence of a long-term persistent form of AF, regardless of gender. Detection of myocardial fibrosis signs is more typical for young patients with the maximum stage at the age of 31 to 40 years.